The collapse of the Weimar Republic Political economy and crisis - Abraham, David 1946- (Princeton Univ. Press, 1981)
Based on the author's thesis, University of Chicago, 1977.
Keywords: Geschichte 1924-1932; Geschichte 1918-1933; Economische politiek; Groupes de pression - Allemagne - Histoire; Lutte des classes - Allemagne - Histoire; Nationaal-socialisme; Politique agricole - Allemagne - Histoire; Politique industrielle - Allemagne - Histoire; Weimar-republiek; Gewerkschaft, Politik; Innenpolitische Geschichte; Sozialdemokratische Partei und Staat; Geschichte; Nationalsozialismus; Wirtschaftspolitik; Agriculture and state -- Germany -- History; Industrial policy -- Germany -- History; Pressure groups -- Germany -- History; Social conflict -- Germany -- History; Wirtschaft; Weimarer Republik; Ende; Staat; Germany - Politics and government - 1918-1933; Deutschland; Hochschulschrift